ANALISIS YURIDIS KEWENANGAN OTORITAS JASA KEUANGAN DALAM PENGATURAN DAN PENGAWASAN TERHADAP LEMBAGA PEMBIAYAAN KONSUMEN - ABDUL RAHMAN SIREGAR (PREMISE LAW JURNAL, 2015)
A consumer financial institution is a part of business activities in the industry of financial services and does business activities to finance the provisions of goods based on consumers’ needs as to finance motor vehicles, home equipment, electronic goods and housing. The consumer financial institution in legal institution in Indonesia is arranged in Book III of the Civil Codes on Agreement, Law No.21/2011 on Authority of Financial Service, PMK No.84/PMK.012/206 on Financing Company, Presidential Regulation No.9/2009 on Financing Institution and Regulations of Authority of Financing Service which arrange business activities of financial institutions. The regulating forms of Authority of Financing Service are the rulings of regulations and policies to business activities to finance consumers and in the form of direct and indirect supervisions of authority of financial service. Breaking the regulations/conditions and the Authority of Financing Service does not fulfill the conditions, the financing company will be given a legal sanction, namely an administrative sanction. Keywords : Authority of Financing Service, Regulating and Supervising, Consumer Financial Institution